Impact of social media marketing on Customers' purchasing intention: with special reference to hotel industry in north central province, sri lanka - Senevirathna, H.P.I.S; Kajanthy, S.; Sathana, V. (University of Jaffna, 2017)
The hotel industry as a whole is being stressed by many forces to use social media marketing rapidly. Hotels are becoming progress with this social media cause to stay up to date with the newest market trends and to cope with its rivals. The purpose of this study is to examine the impact of social media marketing on consumers' purchasing intention in hotel industry. This study is based on the quantitative approach. Convenient sampling technique was used to collect the primary data from the respondents. Cutomers form Hotels in North Central Province of Sri Lanka who are participating in social media marketing were selected for the data collection. Two hundred questionnaires were considered as valid responses. Simple regression analysis was done to identify the impact of dimension of social media marketing towards customers' purchase intention. To further prove the reliability of the data, Cronbach's alpha test, Kaiser-Meyer_olkin (KMO) and Bartlett Test of sphericity were applied in this research. This study reveals that there is a high significant impact of social media marketing on consumers' purchasing intention. This research makes a positive contribution for decision makers in the hospitality industry on the understanding of how the direction of social media marketing influences on customers 'purchasing intention.
Keywords: Social media marketing; Hotel industry; Consumer purchasing intention